Teacher trainers’ perception of employability skills needed for teaching agricultural science in Nigerian secondary schools - Hamid, Abdul (fakulti pendidikan, 2012)
The study determined the trainers’ perception of employability skills needed by graduate’s teacher for teaching Agriculture Science in secondary schools. Two research questions guided the study. The design of this study was a survey research design. The area for this study was Bauchi and Gombe States. The population for this study includes all Agriculture Education lecturers in Nigerian Universities. Purposive sampling was used to select 17 trainers/lecturers as the respondents. The instrument was a structured questionnaire which was validated and pilot tested to obtain its reliability coefficient (Cronbach's Alpha) of 0.98. Data collected was analyzed using AMOS 18 statistical packages for windows. Findings of this study revealed that the trainers perceived that the employability skills needed by the graduate teachers to be successful in teaching agricultural science in secondary schools are important and the graduates are competent in them. It is recommended that all the employability skills be retained or included in the University Agriculture Education curriculum. Agricultural Education being a vocational course, students should be given the opportunity to apply the science they have learned in their course. That means more “hands-on” should be incorporate in the classroom teaching.